PSYCHOPATHY IN ORGANIZATIONAL CONTEXT: A QUALITATIVE ANALYSIS OF SMEs IN KARACHI - Muhammad Zeeshan Khan; Dr. Mustafa Hyder (International Journal of Contemporary Issues in Social Sciences, 2024)
Psychopaths are defined as callous, remorseless and manipulative individuals who lack empathy and conscience. Initially it is difficult to identify them because of their charming personality but when they are promoted to top positions their psychopathic behavior is more noticeable. They exhibit damaging effect on organization which needs to be studied in Pakistan. Current study is based on the exploratory research. Qualitative approach was adopted by conducting semi-structured interviews in the organizations of Karachi. Sample was collected through snowball sampling; seven individuals participated in the research. These interviews aimed at identifying the prevalence of psychopathic traits in the behavior of managers and their implications for organizations and employees. Many researchers have tried to identify corporate psychopaths and unveil the effects of such individuals on different variables like employee well-being, employee withdrawal and organization. The previous research on this subject is based in European and North American context; this research studied this subject in Pakistani context. This research supports the literature on corporate psychopathy by identifying psychopathic traits in managers of organizations in Karachi, Pakistan. This study also supports the implications of corporate psychopathy for organizations and employees found in the literature by identifying the effects these traits have on employees and organizations as reported by the employees.